PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP PEMAHAMAN MATERI PENGAMALAN NILAI-NILAI PANCASILA DI SEKOLAH DASAR - Amryna, Nazila; Nurjanah, Siti; Rika Perdana, Dayu; Nurwahidin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was the low level of understanding of Grade IV studentsat SDN 11 Metro Pusat regarding the material on the implementation of Pancasilavalues. This study aimed to analyze the effect of using comic media on students’understanding of the material on the implementation of Pancasila values. Themethod used in this research was a quasi-experimental design in the form of anonequivalent control group design. The population was determined using apurposive sampling technique consisting of 69 students, while the samplecomprised 46 students. Data were collected through test and non-test techniques inthe form of observation sheets. Hypothesis testing used simple linear regressionwith the results of Fcount> Ftabel, namely (32.840 > 4.32) and a significance valueof 0.000 < 0.05. Therefore, it can be concluded that the use of comic media had asignificant effect on students’ understanding of the material on the implementationof Pancasila values among Grade IV students at SDN 11 Metro Pusat.